Regional economic integration in Mercosur: The role of real and financial sectors - Hem C. Basnet; Gyan Pradhan (Review of Development Finance, 2017)
This study explores economic interdependence in Mercosur by examining common trends and common cycles among key macro-variables representing both the real and financial sectors of the economy. The serial correlation common features test reveals that the key macroeconomic variables (real output, investment, and intra-regional trade) share common trends in the long run suggesting that macroeconomic interdependence in the Mercosur economies is strong. The exchange rates demonstrate co-movement in the long run as they share a single common trend. These finding suggests that these economies cannot swing away from long-run equilibrium for an extended duration; they will be brought together by their common trends. Similarly, each variable under consideration shares common cycles lending support to the notion of short-run synchronous movement. The trend-cycle decomposition results reveal that the cyclical movements of real output and trade are synchronized with a high degree of positive correlations. Our overall findings thus provide justification and optimism for deeper economic integration among Mercosur countries.
Keywords: F15; F42; 650; Economic integration; Co-movement; Business cycles; Mercosur; Exchange rates